The effects of mental fatigue on sport-specific motor performance among team sport athletes: A systematic scoping review - Yuan, R.; Sun, H.; Soh, K. G.; Mohammadi, A.; Toumi, Z.; Zhang, Z. (Frontiers in Psychology, 2023)
Background: The psychobiological state known as mental fatigue (MF) is by engaging in mentally taxing activities for an extended period, which is typically found in team sports, of the high cognitive demand and unpredictable environment. It increases the perception of effort and influences executive functions, impairing sport-specific performance in athletes. However, the consequences of MF on sport-specific motor performance (SSMP) among athletes in team sports remain unclear.